Proresolving Lipid Mediators and Receptors in Stem Cell Biology: Concise Review. (12th June 2019) - Romano, Mario; Patruno, Sara; Pomilio, Antonella; Recchiuti, Antonio
Summary: Accumulating evidence indicates that stem cells (SCs) possess immunomodulatory, anti-inflammatory, and prohealing properties. The mechanisms underlying these functions are being investigated with the final goal to set a solid background for the clinical use of SCs and/or their derivatives. Specialized proresolving lipid mediators (SPMs) are small lipids formed by the enzymatic metabolism of polyunsaturated fatty acids. They represent a leading class of molecules that actively and timely regulate the resolution of inflammation and promote tissue/organ repair. SC formation of these mediators as well as expression of their receptors has been recently reported, suggesting that SPMs may be involved in the immunomodulatory, proresolving functions of SCs. In the present review, we summarize the current knowledge on SPMs in SCs, focusing on biosynthetic pathways, receptors, and bioactions, with the intent to provide an integrated view of SPM impact on SC biology. Stem Cells Translational Medicine   2019;8:992–998 : Abstract : Scheme of specialized proresolving lipid mediator involvement in stem cell pathobiology. Specialized proresolving lipid mediators binding to its cognate receptor expressed by stem cells (upper left) in conjunction with specialized proresolving lipid mediator generation by stem cells (upper right) can regulate stem cell-governed pathways involved in immunoregulation, inflammation resolution, and tissue repair through interactions with blood as well as resident cells (center).